"Making Life Easier": A Case Study Exploring the Development of Adaptive Apparel Design Innovations from a User-Centered Approach. (4th May 2022) - McBee-Black, Kerri
Abstract: Mindy Scheier, a former fashion designer and mother of a child with a disability, developed adaptive apparel design innovations focused on three categories: (a) magnetic closures; (b) adjustable pant legs, sleeves, and waistband; and (c) the flexibility of donning and doffing using different points of entry. The adaptive design features were incorporated into a first-of-its-kind adaptive children's wear line collaboration with Tommy Hilfiger ® in 2016. Scheier's adaptive design features and her collaboration with Tommy Hilfiger ® were well documented and have influenced additional adaptive apparel lines in mainstream fashion. The goal of this study was to gain an in-depth and contextualized understanding of Scheier's design process to determine how she developed her adaptive apparel design innovations using a user-focused approach. To achieve this goal, a case study was deployed. This study revealed that Scheier included the PWD (people with disabilities) user in every stage of her design process by building trust and allyship with the PWD population. Further, Scheier had to balance the needs of the PWD user with that of the apparel industry to ensure her adaptive design features were included in mainstream apparel.